High-Fat Diet-Induced Weight Gain, Behavioral Deficits, and Dopamine Changes in Young C57BL/6J Mice - Han, Jian; Nepal, Pragya; Odelade, Anuoluwapo; Freely, Frederick D.; Belton, Destiny M.; Graves, Joseph L.; Maldonado-Devincci, Antoniette M. (Frontiers in Nutrition, 2021)
Chronic exposure to a high-fat diet (HFD) may predispose individuals to neuropathologies and behavioral deficits. The objective of this study was to determine the temporal effects of a HFD on weight gain, behavioral deficits, and dopamine changes in young mice. One-month old C57BL/6J male and female mice were fed either a control diet (containing 10% calories from fat) or a HFD (containing 45% of calories from fat) for 5 months. Physiological measures such as food consumption, body weight, blood glucose, and behaviors such as motor activity, sensorimotor integration, and anxiety-like behaviors were evaluated monthly. Dopamine (DA), dopamine receptor D2 (DRD2), and dopamine transporter (DT) protein expression levels were measured in the midbrain after 5 months of dietary exposure. Results showed that body weight was significantly greater in the HFD-exposed group compared to the control-group at the end of the 4th month, while food consumption was similar in both groups. For behavioral effects, the HFD group exhibited a significant decrease in motor activity in the open field test after 3 months, and rearing frequency after 4 months of dietary exposure. The HFD group also showed deficits in sensorimotor integration after 3 months. Specifically, chronic HFD exposure increased contact time and time to remove the first adhesive tape in the adhesive-tape removal test (p < 0.05). Furthermore, the HFD group showed significant deficits in balance/coordination compared to the control group after 4 months of dietary exposure using the beam traverse test, and increased anxiety-like behavior tested by both the open field and light/dark box tests (p < 0.05). Neurochemical measurements showed that HFD-exposed mice had significantly higher midbrain DA and DRD2 protein levels compared to the control group after 5 months of dietary exposure (p < 0.05). These results indicate that the impact of HFD on the C57BL/6J mouse strain began at the 3rd month of dietary exposure. Behavioral deficits occurred at a similar time point as increased body weight, at about 3–4 months. Overall, this study provides a critical understanding on how HFD-induced changes in weight gain and behavioral deficits in this strain occur over time. The behavioral changes support the idea that changes also occurred in neurochemical pathways such as dopamine dysregulation.